Debating their beliefs to victory - Abdul Latiff, Muhamad Farid (Universiti Selangor (UNISEL), 2017)
Debating is more often than not viewed as an aggressive and intimidating contest of argumentation between two teams or individuals. It also receives a plethora of public backlashes since debating is not widely acknowledged and accepted as part of our culture. However, more importantly, debate is an essential tool for developing and maintaining democracy and open societies. It is more than a mere verbal activity, debating manifests the archetypes of reasoned arguments, tolerance towards differing viewpoints, and rigorous self-examination. And yes, without a doubt, debating is liberating; it sets you free from holding your thoughts back and people’s perception of you.